CHEMICAL COMPOSITION OF ARTEMISIA ADAMSII BESS. ESSENTIAL OIL FROM THE FLORAS OF THE BURYAT REPUBLIC (RUSSIA) AND MONGOLIA - T. E. Randalova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Artemisia adamsii Bess. is a perennial herb. It belongs to the Compositae Giseke family. Artemisia adamsii grows in meadows, steppes, rocky hills, along roads and on solonetz. The plant grows in the Siberian region of Russia (Buryatia and Chita region), in Mongolia and China (Western Manchuria). Infusion, decoction of leaves, inflorescences, herbs are used in traditional Tibetan and folk medicine as antipyretic. We present the results of a comparative analysis of the chemical composition of essential oil of Artemisia adamsii of Russian (Buryatia) and Mongolian floras. Raw materials were collected during expeditions in 2014 in Ivolginsky district of the Republic of Buryatia (Russia) and in Khentei aimag (Mongolia). Samples of essential oil were obtained from the dried aerial parts of the plant by hydrodistillation. Essential oils are liquids with yellow-green to yellow colors. Oilyield was from 0.4 to 1.0 % in terms of the air-dry feed. Essential oils were investigated by chromatography-mass spectrometry on chromatograph Agilent Packard HP 6890 with detector quadrupole mass spectrometer MSD 5973N. More than 120 compounds were found in the composition of the essential oil of Artemisia adamsii and about 85 % was identified. 1,8-cineole (8.6-40.8 %), terpinene-4-ol (4.3-5.7 %), camphor (2.6-43.6 %) bicyclogermacrene (2.2-6.1 %), spatulenol (1.9-11.0 %) are the dominant components. Camphor, 1,8-cineole, terpineol-4, spatulenol possess antibacterial and anti-inflammatory activities.